Using macroecological species distribution models to estimate changes in the suitability of sites for threatened species reintroduction. Issue 1 (12th March 2021) - Bellis, Joe; Longden, Mike; Styles, Joshua; Dalrymple, Sarah
Abstract: 1. Species reintroductions often aim to establish populations of threatened taxa over the long‐term. However, climate change may jeopardize reintroduction efforts by altering the conditions of a recipient site beyond the tolerances of the focal species. To aid the selection of recipient sites that will retain their suitability under climate change, species distribution models (SDMs) have been proposed as a method of locating areas with a greater likelihood of facilitating species persistence. 2. We applied SDMs to predict macroclimatic suitability changes for 13 threatened plant and invertebrate species considered for reintroduction at four lowland raised bog sites undergoing restoration. We estimated suitability based on current and projected future conditions under two greenhouse gas concentration scenarios – one low (RCP2.6) and one high (RCP8.5) – using three general circulation models, for the period 2041–2060. 3. When considering current predicted suitability, our models indicated that nine species were viable candidates for reintroduction to at least one of the restoration sites. But when accounting for potential future changes in suitability, the number of candidates was reduced to seven species, based on the RCP8.5 climate change scenario. While three of the sites received consistently similar predictions of suitability across species and scenarios, the most northerly site, Red Moss, received divergent suitability predictions for some species. This site is predicted to remain suitable for Metrioptera brachyptera and Genista anglica under at least one scenario despite substantial losses forecast across the rest of their U.K. ranges, suggesting that it could act as a macroclimatic refuge as climate change advances. 4. The findings presented here made a valuable contribution to the reintroduction planning process, by facilitating the prioritization of reintroduction efforts towards species with a greater likelihood of establishing long‐term populations at the prospective recipient sites. Abstract : Climate change may jeopardise reintroduction efforts by altering the conditions of a recipient site beyond the tolerances of the reintroduced population. We use macroecological species distribution models to predict the current and future suitability of a series of raised bog restoration sites for 13 species earmarked for reintroduction. Model outputs facilitated the prioritisation of reintroduction efforts towards seven species with a greater likelihood of establishing long‐term populations.